2013
DOI: 10.2478/ama-2013-0021
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity of a Photogrammetric Method in Formability Analysis

Abstract: Nowadays is a possible to implement numerical simulation and photogrammetric inspection to the complex process chain of inspection. In the recent years there has been significant progress in accuracy improving of these methods of inspection in pre-production or post-production stage of manufacturing. This article discusses these two methods from sensitivity and comparison point of view. Most attention has been paid to the photogrammetric method and his sensitivity to using different approaches. Results were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…The Argus uses a 12-megapixel camera sensor and is mainly used to measure deformations in the processes of sheet metal forming in order to assess the quality of sheet metal products, or to conduct a comparative analysis of mathematical and physical modelling [ 41 , 42 , 43 ]. When measuring drawpieces, the position of the camera recording the image is changed in at least two planes [ 44 ]. In each camera position, the object relative to the camera is rotated by a specific angle.…”
Section: Methodsmentioning
confidence: 99%
“…The Argus uses a 12-megapixel camera sensor and is mainly used to measure deformations in the processes of sheet metal forming in order to assess the quality of sheet metal products, or to conduct a comparative analysis of mathematical and physical modelling [ 41 , 42 , 43 ]. When measuring drawpieces, the position of the camera recording the image is changed in at least two planes [ 44 ]. In each camera position, the object relative to the camera is rotated by a specific angle.…”
Section: Methodsmentioning
confidence: 99%
“…6. Coming out from assumptions presented in the literature [12] the force F BL we can calculate as follows:…”
Section: Methodsmentioning
confidence: 99%
“…They have found that this system does not provide acceptable accuracy in the measurement of certain areas of the drawpiece, especially those that include internal, small radii. Slota et al [12] tested the sensitivity of the Argus system by using a photo or a video camera to take the pictures, using the anti-reflexive spray and comparing the strains computed by the numerical simulation and ones measured by the Argus system. Authors have observed great sensitivity of different factors on the measured values of strains, such as the time of etching, etching process parameters, type of measuring grid, quality of sheet surface in pre-production phase and type of used camera, application of developer, interpolation parameters, different lighting conditions, angles of the camera view and the number of captured pictures in post-production phase.…”
Section: Introductionmentioning
confidence: 99%
“…Digitizing objects is the main activity in the process of reverse engineering for engineering production. This process is possible due to scanning devices, known as 3D scanners, which enable the conversion of real three-dimensional objects into the digital form [9], [10].…”
Section: Introductionmentioning
confidence: 99%